ChemInform Abstract: Solid Solution Studies of Layered Honeycomb‐Ordered Phases O3—Na3M2SbO6 (M: Cu, Mg, Ni, Zn). Issue 27 (13th June 2013) - Schmidt, Whitney; Berthelot, Romain; Sleight, A. W.; Subramanian, M. A.
Abstract Complete solid solutions Na3M12‐xM2x SbO6 (M1, M2: Cu, Mg, Ni, Zn) are characterized by XRD, magnetic susceptibility, and optical measurements.